Religiosity as a factor of social-emotional resilience and personal growth during the COVID-19 pandemic in Croatian adolescents - Filipović, Ana Thea (Journal of Religious Education, 2023)
The coronavirus pandemic and measures to protect against the spread of infection have had a specific effect on individual age groups. This research is focused on adolescents (from 13 to 19 years old) because young people at that age are already going through a developmental crisis, which is further intensified by pandemic circumstances. The survey, conducted in Croatia from December 2020 to February 2021 (N = 857), sought to identify the possible personalizing of faith in adolescents as well as the impact of religiosity on their coping with the pandemic, especially in terms of social-emotional resilience and personal growth. In addition to descriptive indicators, the analysis used inferential procedures to check the statistical significance of differences (t-test, ANOVA), as well as connections and determinations between variables (correlation and regression analysis). The hypotheses were confirmed that the faith of religious adolescents became more personal and that it had a positive effect on psycho-social resilience and personal growth, but in combination with family cohesion, which on the one hand was stimulated by religiosity, and on the other, influenced personal growth.